Catalytic ozonation of oxalate with a cerium supported palladium oxide: An efficient degradation not relying on hydroxyl radical oxidation - Zhang, T.; Li, W.; Croué, Jean-Philippe (American Chemical Society, 2011)
The cerium supported palladium oxide (PdO/CeO 2) at a low palladium loading was found very effective in catalytic ozonation of oxalate, a probe compound that is difficult to be efficiently degraded in water with hydroxyl radical oxidation and one of the major byproducts in ozonation of organic matter. The oxalate was degraded into CO 2 during the catalytic ozonation. The molar ratio of oxalate degraded to ozone consumption increased with increasing catalyst dose and decreasing ozone dosage and pH under the conditions of this study. The maximum molar ratio reached around 1, meaning that the catalyst was highly active and selective for oxalate degradation in water. The catalytic ozonation, which showed relatively stable activity, does not promote hydroxyl radical generation from ozone. Analysis with ATR-FTIR and in situ Raman spectroscopy revealed that 1) oxalate was adsorbed on CeO 2 of the catalyst forming surface complexes, and 2) O 3 was adsorbed on PdO of the catalyst and further decomposed to surface atomic oxygen (*O), surface peroxide (*O 2), and O 2 gas in sequence. The results indicate that the high activity of the catalyst is related to the synergetic function of PdO and CeO 2 in that the surface atomic oxygen readily reacts with the surface cerium-oxalate complex. This kind of catalytic ozonation would be potentially effective for the degradation of polar refractory organic pollutants and hydrophilic natural organic matter.